The Warburg Trap: a novel therapeutic approach for targeting osteosarcoma - Fellenberg, Jörg; Losch, Sarina; Tripel, Elena; Lehner, Burkhard; Melnik, Svitlana (Cells, 2024)
Although urgently needed, no significant improvements in osteosarcoma (OS) therapy have been achieved within the last decades. Here, we present a new therapeutic approach based on drug combinations consisting of mitochondrial complex I (MCI) inhibitors and ionophores that induce cancer cell-specific cell death based on a modulation of cellular energy metabolism and intracellular pH (pHi) named the Warburg Trap (WT). The effects of several drug combinations on intracellular pH, cell viability, colony-forming capacity and expression of WNT-target genes were analysed using OS cell lines and primary human osteoblasts (HOB). Tumour take rates and tumour volumes were analysed in vivo using a chicken chorioallantoic membrane assay (CAM). Several WT drug combinations induced the intracellular acidification and apoptotic cell death in OS cells, whereas HOBs tolerated the treatment. A significant inhibition of the colony-forming ability of OS cells and downregulation of WNT-target genes suggest that cancer stem cells (CSCs) are also targeted by the WT approach. In vivo, we observed a significant reduction in the tumour take rates in response to WT drug treatment. Our data suggest that the Warburg Trap is a promising approach for the development of a novel and effective OS therapy to replace or supplement the current OS chemotherapy.